Leadership Communication Through Whatsapp Application In A Primary School - Ahmad, Asma (Selangor Humaniora Review, 2019)
In an organization such as the school, leadership style is often related to the success of the head of the school in leading and managing the staff. One important factor in any leadership style is communication between the superior and his or her subordinates. The study examines a leadership communication tool using ‘WhatsApp’ (mobile instant messaging application) in everyday communication between the staff and administrator of the school. The consistency and frequency of messaging texts were observed and it was found that the criteria of messaging can be classified into two categories which are social communication and official communication. Data was collected through survey questionnaire, interviews and observations and documents on the text conversations in the WhatsApp application of participants show that, leadership communication through WhatsApp application is useful and effective in the school administration and management and also in maintaining good relationship between superiors and subordinates.